Oferta rozrywkowa stacji radiowych w internecie na przykładzie Radia Eska - Czarnek, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Commercial radio stations – from a marketing point of view – consider delivering entertainment to listeners to be their main aim. In order to carry this out, they use not only programmes broadcast daily, but also opportunities provided by the phenomenon of convergence. The subject of this article is the types of convergence seen in entertainment created by radio makers. These are discussed based on the example of Radio Eska – a formatted radio station, targeted at young listeners and directing its message to their needs.